The Impact of Device Innovation on Clinical Outcomes in Expander-based Breast Reconstruction. Issue 12 (December 2019) - Momeni, Arash; Li, Alexander Y.; Tsai, Jacqueline; Wan, Derrick; Karin, Mardi R.; Wapnir, Irene L.
Abstract : Background: Staged expander-based breast reconstruction represents the most common reconstructive modality in the United States. The introduction of a novel tissue expander with an integrated drain (Sientra AlloX2) holds promise to further improve clinical outcomes. Methods: Patients who underwent immediate expander-based pre-pectoral breast reconstruction were identified. Two cohorts were created, that is, patients who underwent placement of a conventional tissue expander [133MX (Allergan)] (Group 1) versus AlloX2 (Sientra) (Group 2). The study endpoint was successful completion of expansion with the objective being to investigate differences in outcome following expander placement. Results: Fifty-eight patients underwent 99 breast reconstructions [Group 1: N = 24 (40 breasts) versus Group 2: N = 34 (59 breast)]. No differences were noted for age ( P = 0.586), BMI ( P = 0.109), history of radiation ( P = 0.377), adjuvant radiotherapy ( P = 1.00), and overall complication rate ( P = 0.141). A significantly longer time to drain removal was noted in Group 1 ( P < 0.001). All patients with postoperative infection in Group 1 required surgical treatment versus successful washout of the peri-prosthetic space via the AlloX2 drain port in 3 of 5 patients in Group 2 ( P = 0.196). Furthermore, both cases of seroma in Group 1 required image-guided drainage versus in-office drainage via the AlloX2 drain port in 1 patient in Group 2 ( P =0.333). Conclusion: The unique feature of the AlloX2 provides surgeons easy access to the peri-prosthetic space without altering any of the other characteristics of a tissue expander. This resulted in a reduced time to drain removal and facilitated management of postoperative seroma and infection.